2017
DOI: 10.1016/s0140-6736(17)31462-9
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cancer

Abstract: SummaryOesophageal cancer is a clinically challenging disease requiring a multidisciplinary approach.The extensive treatment may be associated with serious limitations in health-related quality of life and yet still a poor prognosis. Recent decades have witnessed a gradual improvement in prognosis in many countries. Endoscopic procedures have increasingly been used in the treatment of premalignant and early oesophageal tumours. Neoadjuvant therapy with chemotherapy or chemoradiotherapy has supplemented surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
843
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 930 publications
(911 citation statements)
references
References 159 publications
8
843
0
8
Order By: Relevance
“…The number of harvested lymph nodes was not significantly different (31 vs. 33, P=0.198) between the two groups, satisfying the requirements for the Worldwide Esophageal Cancer Collaboration data (12,13). Lagerson and colleagues suggested that a higher number of harvested lymph nodes provided better survival in esophageal cancer (2). Many surgeons believe that MIE is inappropriate in obtaining adequate lymph node harvesting and that insufficient lymph node harvesting leads to a lower incidence of pulmonary complication outcomes.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The number of harvested lymph nodes was not significantly different (31 vs. 33, P=0.198) between the two groups, satisfying the requirements for the Worldwide Esophageal Cancer Collaboration data (12,13). Lagerson and colleagues suggested that a higher number of harvested lymph nodes provided better survival in esophageal cancer (2). Many surgeons believe that MIE is inappropriate in obtaining adequate lymph node harvesting and that insufficient lymph node harvesting leads to a lower incidence of pulmonary complication outcomes.…”
Section: Discussionmentioning
confidence: 62%
“…However, esophagectomy is still the mainstay treatment modality for resectable esophageal cancer, despite its high operative mortality and morbidity (2). Moreover, pulmonary complications, such as pneumonia, ARDS, and other respiratory complications, despite recent progress in anesthetic procedures and postoperative care, still remain to be the most adverse events following esophagectomy (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esophageal cancer is one of the most aggressive cancers of the digestive tract 1. Historically, the most important therapy has been esophagectomy with extended lymphadenectomy 2, 3.…”
Section: Introductionmentioning
confidence: 99%